Small-scale spatial variability of flame retardants in indoor dust and implications for dust sampling - Jílková, Simona; Melymuk, Lisa; Vojta, Šimon; Vykoukalová, Martina; Bohlin-Nizzetto, Pernilla; Klánová, Jana (Chemosphere, 2018)
Indoor dust is often used to evaluate levels of organic compounds indoors, particularly for compounds with indoor sources, such as flame retardants (FRs). Yet there are uncertainties about the type of information that can be obtained from indoor dust. This study reports detailed dust sampling to assess spatial variability in indoor dust concentrations, the relationship between FR sources and dust, and the implications when interpreting dust concentrations. Multiple dust samples were collected from a range of surface types in three large rooms: a residential flat, a university seminar room, and a university computer room. Samples were analysed for polybrominated diphenyl ethers (PBDEs), novel halogenated flame retardants (NFRs) and organophosphate esters (OPEs). FR levels in dust varied significantly between and within rooms. Levels typically ranged over one order of magnitude within a room, and up to four orders of magnitude for a few OPEs. The spatial distribution of FRs related (in some cases) to proximity to sources, surface properties, and dust surface loadings. Differences also existed between surface and floor dusts, e.g., the contribution of TBOEP to ∑OPEs was higher in floor than surface dust, which has implications for human exposure assessment; adults typically have more contact with elevated surfaces, while young children have greater contact with floor surfaces. Overall, significant spatial heterogeneity exists in indoor dust, even in seemingly homogeneous indoor spaces, thus hampering comparability between studies and locations when single samples are collected. Composite samples are strongly recommended to limit the influence of spatial heterogeneity.
Keywords: Environmental Monitoring; Flame retardants; monitorování životního prostředí; prach; Flame Retardants; Dust; Humans; retardanty hoření; lidé; Sampling methods; Spatial variability; Indoor dust; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor